A wrinkle-resistant, moisture-absorbing and quick-drying cotton fabric

CN122879974APending Publication Date: 2026-10-09FAST FASHION (GUANGZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611285229.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,这些传统整理方法往往顾此失失:追求高抗皱性通常会严重破坏纤维素的天然羟基结构或导致纤维大幅脆化,造成面料强力严重下降、手感发硬以及吸水性能剧烈衰减;而单纯涂布吸湿速干整理剂又难以从根本上改善面料的折皱回复性能,且整理层在多次洗涤后极易耐洗性失效

Benefits of technology

(1)抗皱及易打理性能提高。通过在棉纤维内部构建硼酸酯交联结构,限制纤维素大分子链在反复形变过程中的不可逆滑移,并利用硼酸酯结构的动态交换能力实现局部应力重新分配,从而提高棉纤维的折皱回复能力,降低面料洗涤及穿着后的残余褶皱。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879974A_ABST
    Figure CN122879974A_ABST
Patent Text Reader

Abstract

The application provides an easy-care wrinkle-resistant moisture-absorbing and quick-drying cotton fabric, and belongs to the technical field of fabrics. The cotton fabric is made of modified cotton fibers, the interior of the modified cotton fibers is formed with a borate cross-linking structure, the surface and the near surface layer are grafted with a hydrophilic copolymer containing non-ionic and ionic hydrophilic structure units, and the outer surface is formed with a micro-nano rough structure. The hydrophilic copolymer forms a decreasing grafting density gradient from inside to outside along the radial direction of the cotton fiber, and the micro-nano rough structure is composed of micron-scale and nano-scale fluctuation units. The application constructs a synergistic structure at different scales of the fiber through boron compound cross-linking, pre-soaking and permeation, surface layer dilution grafting and silicon hydride phase separation hydrolysis and condensation, so that the modified cotton fiber has dynamic stress dissipation and self-adaptive recovery ability, realizes directional migration and rapid spreading and evaporation of water, and endows the cotton fabric prepared therefrom with excellent easy-care wrinkle resistance and moisture-absorbing and quick-drying performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fabric technology, and in particular relates to an easy-care, wrinkle-resistant, moisture-wicking and quick-drying cotton fabric. Background Technology

[0002] Cotton fiber, as a natural cellulose fiber, has long been widely used in various textiles and clothing fabrics due to its excellent hydrophilicity, breathability, moisture absorption, and comfortable feel against the skin. However, unmodified pure cotton fabrics generally suffer from physical defects during daily wear and washing, such as easy wrinkling, poor wrinkle recovery, slow drying after absorbing water, and stickiness when wet. These problems significantly limit the high-end application of pure cotton fabrics and their use in sports, outdoor, and fast-paced lifestyle scenarios.

[0003] The fundamental reason why pure cotton fabric wrinkles easily lies in the aggregated structure of its internal cellulose macromolecules. The main chemical component of natural cotton fiber is cellulose, composed of anhydrous glucose residues, whose molecular chains contain a large number of polar hydroxyl groups (-OH). When not subjected to external force, these hydroxyl groups form a dense network of hydrogen bonds between molecular chains and microfibrils, maintaining the stability of the fiber morphology. However, when pure cotton fabric is subjected to bending, compression, stretching, or other external forces during wear or washing, the cellulose macromolecular chains undergo relative slippage, and some of the original hydrogen bonds break. During this process, if there is moisture or temperature change in the environment, the cellulose chain segments will reform strong intermolecular hydrogen bonds in the new spatial locations. When the external force is removed, because these newly formed hydrogen bonds prevent the molecular chains from returning to their original conformation, macroscopically, this manifests as residual wrinkles on the fabric surface that are difficult to eliminate on their own. Although traditional ironing processes can use temperature and humidity to break and reform hydrogen bonds to restore smoothness, the fabric will repeatedly wrinkle after being subjected to force or washing again, seriously affecting the appearance of clothing and the convenience of daily maintenance.

[0004] While pure cotton fabric possesses excellent absorbency and moisture transfer properties, its mechanism for interacting with moisture has inherent limitations. The abundant polar hydroxyl groups in the natural cotton fiber structure can rapidly bind with water molecules, giving pure cotton fabric a very high equilibrium moisture regain and good initial absorbency. However, this strong hydrogen bonding also means that once moisture enters the cotton fiber, it is easily "locked" in by polar groups or trapped in the blind pores within the fiber, making it difficult for moisture to migrate efficiently and quickly between fiber networks. When the human body sweats profusely, pure cotton fabric often quickly absorbs a large amount of sweat and reaches saturation. However, due to the lack of an efficient mechanism to guide moisture to the outer layer, a large amount of liquid sweat remains trapped inside the fabric on the skin-contact side. This not only leads to a significant increase in fabric weight and a sharp decrease in breathability but also causes the fabric to cling tightly to the skin, producing a strong damp, cold, and sticky feeling, greatly reducing wearing comfort.

[0005] Another prominent drawback closely related to its moisture absorption performance is the extremely slow drying speed of pure cotton fabrics. The evaporation rate of moisture in a fabric depends primarily on the effective contact area between the liquid and air, as well as the efficiency of moisture supply from the fabric's interior to its exterior surface. For traditional pure cotton fabrics, moisture firmly absorbed by the fibers is difficult to spread automatically to the outer surface, failing to form a large-area thin liquid film. Simultaneously, the swelling of fibers after absorbing water often alters the size of the capillary channels between fibers, even causing partial blockage, hindering the continuous evaporation and dissipation of internal moisture to the external environment. This characteristic of "easy absorption, difficult conduction, and slow dissipation" results in a long drying period for pure cotton fabrics after washing, making it particularly difficult to keep dry in high-temperature, high-humidity environments or during strenuous exercise and sweating, and making them extremely prone to bacterial growth and odor.

[0006] To address these issues, traditional textile technologies typically employ chemical finishing methods, such as using resin finishing agents to treat cotton fabrics for wrinkle resistance, or using functional finishing agents like silicone oil and fluorinated polymers for post-finishing. However, these traditional finishing methods often have drawbacks: pursuing high wrinkle resistance often severely damages the natural hydroxyl structure of cellulose or causes significant fiber embrittlement, resulting in a severe decrease in fabric strength, a stiff hand feel, and a drastic reduction in water absorption; while simply applying moisture-wicking and quick-drying finishing agents cannot fundamentally improve the fabric's wrinkle recovery performance, and the finished layer is prone to loss of wash resistance after repeated washing. Summary of the Invention

[0007] The first objective of this invention is to provide modified cotton fibers, including a cotton fiber matrix, wherein a borate ester crosslinking structure is formed inside the cotton fiber matrix, a hydrophilic copolymer is grafted onto the surface and near-surface layer of the cotton fiber matrix, and a micro-nano rough structure is formed on the outer surface of the cotton fiber. The borate ester crosslinking structure is formed by a polyboron structure compound having at least two boric acid groups that can form borate ester bonds with the cellulose hydroxyl groups, and the content of the borate ester crosslinking structure is 0.05-0.40 mmol / g; The hydrophilic copolymer is formed by copolymerizing a first hydrophilic olefinic unsaturated monomer and a second hydrophilic olefinic unsaturated monomer. The first hydrophilic olefinic unsaturated monomer and the second hydrophilic olefinic unsaturated monomer respectively form a nonionic hydrophilic structural unit and an ionic hydrophilic structural unit. The nonionic hydrophilic structural unit and the ionic hydrophilic structural unit are distributed along the molecular chain of the hydrophilic copolymer and together constitute a hydrophilic graft structure. The grafting amount of the hydrophilic copolymer is 2wt%-15wt%; the hydrophilic copolymer forms a decreasing grafting density gradient from the inside to the outside along the radial direction of the cotton fiber, and the ratio of the maximum grafting density to the minimum grafting density of the hydrophilic copolymer in the radial direction of the cotton fiber is 1.5-3.0. The outer surface of the cotton fiber has a multi-scale surface undulation structure. The height difference between adjacent peaks and valleys of the micron-scale undulation units of the multi-scale surface undulation structure is 0.2-1.0 μm, and the projection distance between adjacent peaks and valleys along the surface of the cotton fiber is 0.5-3.0 μm. The surface of the micron-scale undulation units further has nano-scale undulations, and the height difference between adjacent peaks and valleys of the nano-scale undulations is 20-200 nm. The arithmetic mean roughness Ra of the outer surface of the cotton fiber is 80-500 nm. In the outer surface of the cotton fiber, the surface region that satisfies the height difference characteristics at the micron and / or nanoscale accounts for 15%-70% of the total area of ​​the outer surface of the cotton fiber.

[0008] Preferably, the cotton fiber matrix is ​​natural cotton fiber, the cellulose mass fraction in the cotton fiber matrix is ​​90%-98%, and the cotton fiber matrix has a cellulose I crystal structure with a crystallinity of 55%-75%.

[0009] Preferably, in the borate ester crosslinking structure, boron atoms react with the ortho-hydroxyl groups at the C2 and C3 positions of cellulose to form a five-membered cyclic borate ester bond.

[0010] In the cotton fiber matrix, the cellulose hydroxyl groups that participate in the formation of the borate ester crosslinking structure account for 5-20% of the total cellulose hydroxyl groups.

[0011] Preferably, in the hydrophilic copolymer, the molar ratio of nonionic hydrophilic structural units derived from the first hydrophilic olefin unsaturated monomer to ionic hydrophilic structural units derived from the second hydrophilic olefin unsaturated monomer is 1:0.2-1:1.5.

[0012] Preferably, the weight-average molecular weight of the hydrophilic copolymer is 5000-50000; the first hydrophilic olefin unsaturated monomer is an olefin unsaturated monomer with a nonionic hydrophilic structure, and the second hydrophilic olefin unsaturated monomer is an olefin unsaturated monomer with an ionic hydrophilic structure.

[0013] Preferably, the ratio of the height difference between adjacent peaks and valleys of the micron-scale undulation unit to the height difference between adjacent peaks and valleys of the nano-scale undulation is 5-50; in the actual measurement area on the outer surface of the cotton fiber, the area with the micron-scale undulation and / or nano-scale undulation accounts for 15-70% of the total area of ​​the actual measurement area.

[0014] Preferably, the micro-nano rough structure is formed by introducing a hydrolyzable silane precursor and a pore-inducing agent onto the surface of the hydrophilic copolymer graft layer, followed by phase separation, hydrolysis, and condensation to form a silicon-containing nanostructure, and then by controlled shrinkage treatment.

[0015] A second objective of this invention is to provide a method for preparing the aforementioned polyester fabric, comprising the following steps: S1. Crosslinking treatment: The cotton fiber is impregnated in a crosslinking solution containing the multiboron structure compound, so that the multiboron structure compound penetrates into the cotton fiber and undergoes a borate esterification reaction with the cellulose hydroxyl groups to form a borate ester crosslinking structure. The content of the borate ester crosslinking structure is controlled to be 0.05-0.40 mmol / g. S2, Gradient Grafting: The cotton fibers treated in S1 are immersed in a grafting reaction solution containing the first hydrophilic olefinic unsaturated monomer, the second hydrophilic olefinic unsaturated monomer, and a free radical initiator. Pre-wetting is first performed at 30-40℃ for 10-30 minutes to allow the monomers to fully penetrate the cotton fibers. Then, the monomer concentration on the outermost surface of the cotton fibers is reduced by surface cleaning or dilution. Grafting polymerization is then carried out at 45-60℃ for 20-90 minutes, resulting in a decreasing grafting density gradient of the hydrophilic copolymer along the radial direction of the cotton fibers from the inside out. The grafting amount of the hydrophilic copolymer is controlled at 2-15 wt%, and the ratio of the maximum grafting density to the minimum grafting density is controlled at 1.5-3.0. S3, In-situ construction of silane: Cotton fibers treated with S2 are contacted with a silane precursor containing hydrolyzable alkoxy groups and a pore-inducing agent, so that the silane precursor undergoes phase separation hydrolysis and condensation on the surface of the hydrophilic copolymer graft layer to form a silicon-containing nanostructure. S4. Controlled shrinkage: The cotton fibers treated in S3 are dehydrated and dried in stages to cause controlled shrinkage of the hydrophilic copolymer graft layer and its surface silicon-containing nanostructures, forming a multi-scale surface undulation structure on the outer surface of the cotton fibers, thus obtaining the modified cotton fibers.

[0016] The third objective of this invention is to provide an easy-care, wrinkle-resistant, moisture-wicking, and quick-drying cotton fabric, which is formed by spinning and weaving the aforementioned modified cotton fibers.

[0017] This invention achieves multi-level structural regulation of natural cotton fibers, constructing functional structures at the macromolecular scale of cellulose, the polymer grafting scale, and the micro / nanoscale of the fiber surface, thereby enabling the cotton fibers to simultaneously possess wrinkle-resistant, moisture-absorbing, and fast-drying properties. Its mechanism of action mainly includes the following aspects.

[0018] 1. The regulatory mechanism of borate ester crosslinking structure on the wrinkle resistance of cotton fibers Natural cotton fibers are mainly composed of cellulose, and the cellulose macromolecular chains form a relatively stable aggregate structure through a large number of hydrogen bonds. When cotton fibers are bent, compressed or stretched, the cellulose macromolecular chains and their microfibril structures will undergo local displacement, some of the original hydrogen bonds will break and reform in new spatial positions; when the external force is removed, if the macromolecular chains fail to fully recover to their original conformation, residual deformation will form, which will eventually manifest as wrinkles in the fabric.

[0019] This invention introduces a multi-boron compound with at least two borate groups into the interior of cotton fibers, causing the borate groups to undergo a borate esterification reaction with the hydroxyl groups of cellulose, forming a borate ester crosslinking structure between different cellulose macromolecular chains. This crosslinking structure provides new intermolecular connection points outside the original hydrogen bond network of cellulose, enabling restricted spatial connections between adjacent cellulose macromolecular chains, thereby reducing the possibility of large-scale irreversible slippage of cellulose chain segments under external forces.

[0020] Meanwhile, borate ester bonds possess certain dynamic bond exchange characteristics. Under humid heat, washing, or external force, borate ester bonds can undergo a certain degree of reversible dissociation and recombination, allowing localized stress to redistribute among crosslinking nodes, rather than concentrating on a single cellulose chain segment or localized hydrogen bond regions. After the external force is removed, the borate ester crosslinking structure is re-established, thus facilitating the restoration of the cellulose macromolecular chain and microfiber structure to a more stable original conformation.

[0021] Therefore, this invention does not simply increase the rigidity of cotton fibers by increasing irreversible crosslinking points, but rather utilizes the borate ester crosslinking structure with dynamic response characteristics to restrict the irreversible slippage of cellulose segments while retaining a certain structural adjustment capability. This improves wrinkle recovery performance while reducing the adverse effects of excessive rigidity on fiber flexibility and strength retention.

[0022] 2. Hygroscopic mechanism of synergistic effect between nonionic and ionic hydrophilic structural units The hydrophilic copolymer grafted onto the surface and near-surface of cotton fibers is formed by copolymerization of a first hydrophilic olefinic unsaturated monomer and a second hydrophilic olefinic unsaturated monomer, which respectively provide nonionic hydrophilic structural units and ionic hydrophilic structural units.

[0023] Among them, nonionic hydrophilic structural units can form hydrogen bonds or dipole interactions with water molecules through polar structures such as hydroxyl groups, amide groups, and ether oxygen, thus generating a continuous affinity for water molecules; while ionic hydrophilic structural units can improve the fiber surface's ability to capture water molecules through electrostatic interactions, ion-dipole interactions, and hydration effects between ionic groups and water molecules.

[0024] Two types of hydrophilic structural units are distributed along the molecular chain of the hydrophilic copolymer, giving the copolymer both nonionic and ionic hydration sites. Compared to a single type of hydrophilic group, this composite hydrophilic structure can maintain stable water molecule binding and migration capabilities over a wider range of aqueous conditions.

[0025] The nonionic hydrophilic structure primarily facilitates the formation of continuous hydrogen-bonded hydration channels, while the ionic hydrophilic structure enhances the initial adsorption and wetting of polar liquids such as sweat. Therefore, the combined effect of these two structures increases the affinity of cotton fibers for liquid water and water vapor, and promotes the migration of moisture from the fiber interior to the fiber surface.

[0026] 3. Mechanism of action of radial grafting density gradient on directional water migration The present invention does not form a uniform thickness of coating layer on the surface of cotton fibers with hydrophilic copolymers, but controls the hydrophilic copolymers to form a decreasing grafting density gradient from the inside to the outside along the radial direction of the cotton fibers. That is, the inside of the fiber and the near-surface layer have a relatively high grafting density of hydrophilic copolymers, while the area near the outermost surface has a relatively low grafting density.

[0027] This structure creates a high density of hydrophilic hydration sites within the cotton fiber. When sweat or ambient moisture enters the fiber, the internal hydrophilic structure can quickly capture and disperse the moisture, reducing the tendency for moisture to form large droplets or accumulate in localized areas. Simultaneously, the radially decreasing grafting density creates a continuous wettability variation between the fiber's interior and exterior, rather than an abrupt hydrophilic / hydrophobic interface.

[0028] In the fabric, numerous modified cotton fibers interweave to form continuous interfiber capillary channels. Water diffuses outward along the fiber radial direction and through interfiber pores under the combined effects of adsorption by the hydrophilic structures within the fibers, interfiber capillary action, and differences in fiber surface wettability. This transforms the traditional "local retention of water after absorption" process in cotton fibers into a continuous water transport process of "absorption—dispersion—migration—surface spreading."

[0029] It is important to emphasize that this radial gradient does not generate an absolute "mechanical pumping pressure" on its own. Instead, it reduces the resistance to moisture migration from the inside to the outside by changing the wetting state, hydration capacity, and capillary transport conditions in different areas of the fiber, thereby improving the moisture-wicking efficiency of the fabric.

[0030] 4. Mechanism of the effect of multi-scale surface undulation structure on moisture absorption and quick-drying performance The outer surface of cotton fibers further develops a multi-scale surface structure with micron-scale and nano-scale undulations. Among them, the micron-scale undulations create significant changes in the surface profile, while the nano-scale undulations are further superimposed on the micron-scale structure surface, thus forming a multi-level scale surface morphology on the outermost side of the fiber.

[0031] This multi-scale structure increases the actual surface area of ​​cotton fibers, allowing water that migrates from the fiber interior to the surface to spread over a larger solid-liquid interface. On the other hand, the micron-scale peak-valley structure can form a continuous micro-scale liquid migration path, while the nano-scale undulations can further change the local wetting state and droplet boundaries, making it easier for water to transform from local droplets into dispersed thin liquid films.

[0032] When moisture migrates to the outer surface of the fiber, the multi-scale undulating structure allows for more thorough spreading of the moisture, thereby reducing local droplet thickness and increasing the liquid-gas contact area. Simultaneously, the hydration sites provided by the hydrophilic copolymer enable rapid spreading of moisture without the formation of large, isolated droplets. Therefore, under the same environmental conditions, moisture can exist on the fiber surface in a thinner, more dispersed liquid film state, which is beneficial for increasing the evaporation rate.

[0033] Among them, the peak-valley height difference, projection distance and nanoscale undulation height of the micron-scale undulation are all within a specific range, and are further controlled by the arithmetic mean roughness Ra and the effective structural area ratio, so that the surface rough structure can provide a sufficient liquid spreading interface, but will not cause water to be retained in the deep concave structure due to excessive roughness.

[0034] 5. Synergistic mechanism between borate ester crosslinking structure, grafting gradient and micro / nano structure The three functional structures of this invention are not independent of each other, but rather work together at different scales.

[0035] The borate ester crosslinking structure improves the structural stability between cellulose macromolecular chains, making cotton fibers less prone to large irreversible deformation during repeated bending, compression and washing, thus helping to maintain the original pore and capillary channel structure inside the fiber.

[0036] The radial grafting density gradient enables the hydrophilic copolymer to form a high density of hydration sites within the fiber, allowing water to migrate gradually from the fiber interior to the exterior; while the multi-scale surface undulation structure further undertakes the function of spreading and evaporating external water. Therefore, the former mainly solves the problem of "how water is absorbed and migrates to the surface", while the latter mainly solves the problem of "how water that reaches the surface spreads and evaporates quickly".

[0037] The stabilizing effect of borate ester crosslinking on fiber morphology reduces the adverse effects of fiber flattening, bending, and pore shrinkage on moisture transport paths during fabric use, allowing the hydrophilic grafted structure and micro / nano surface structure to remain relatively stable after repeated use. This forms a continuous functional chain of "internal structural stability—rapid moisture absorption—radial migration—surface spreading—rapid evaporation," resulting in a synergistic effect between wrinkle resistance, moisture absorption, and quick-drying properties.

[0038] Compared with unmodified natural cotton fibers and cotton fibers treated with a single hydrophilic finish or ordinary anti-wrinkle finish, the present invention has at least the following beneficial effects: (1) Improved wrinkle resistance and easy care performance. By constructing a borate ester cross-linking structure inside the cotton fiber, the irreversible slippage of the cellulose macromolecular chain during repeated deformation is restricted, and the dynamic exchange capacity of the borate ester structure is used to achieve local stress redistribution, thereby improving the wrinkle recovery ability of cotton fiber and reducing residual wrinkles after washing and wearing the fabric.

[0039] (2) Improved moisture absorption capacity. The hydrophilic copolymer has both nonionic and ionic hydrophilic structural units, which can provide multiple types of hydration sites, improve the ability of modified cotton fibers to capture, wet and disperse sweat and water molecules, so that the cotton fabric can maintain the good moisture absorption properties of cotton fibers themselves and further enhance the moisture absorption efficiency.

[0040] (3) Improved moisture transport and drying speed. By forming a hydrophilic copolymer graft density gradient that decreases from the inside to the outside in the radial direction of the cotton fiber, the fiber has a high moisture capture capacity, and the capillary channels between fibers promote the outward migration of moisture; at the same time, the multi-scale surface undulation structure increases the spreading area of ​​moisture after it reaches the fiber surface, thereby improving the moisture evaporation efficiency and achieving a synergistic effect of moisture absorption and quick drying performance.

[0041] (4) Improved stability of moisture-wicking structure. The borate ester cross-linking structure can improve the structural stability of the cellulose network inside cotton fibers, reduce the degree of irreversible collapse of the internal structure of fibers during repeated bending, compression and washing, thus helping to maintain the integrity of capillary channels and hydrophilic grafting structures between fibers.

[0042] (5) Improved surface moisture spreading performance. Micron-scale and nano-scale undulations form a multi-level surface structure, which increases the actual surface area of ​​the fiber without relying on simply increasing the amount of hydrophilic polymer, and promotes the formation of a more dispersed liquid film of water that migrates to the fiber surface, reducing local moisture retention and helping to shorten the drying time of the fabric.

[0043] (6) Synergistic effect of anti-wrinkle and moisture-wicking properties. This invention does not simply use anti-wrinkle finishing agents and moisture-wicking finishing agents in a simple compounding process. Instead, it regulates the structure of the same cotton fiber at three scales: cellulose molecular network, polymer grafting gradient, and surface micro-nano morphology. This allows the three processes of fiber morphology stability, moisture migration, and surface evaporation to work together, thereby achieving a combination of easy care, anti-wrinkle, moisture-wicking, and quick-drying properties while maintaining the basic textile properties of cotton fibers. Attached Figure Description

[0044] Figure 1 The images are 3D topographic maps and cross-sectional profile curves for Examples 1, 9, and 10.

[0045] Figure 2 The FTIR infrared spectra of Examples 1, 2 and the blank cotton fiber matrix after S1, S2 and S3 are shown.

[0046] Figure 3 Five high-resolution scanning electron microscope (FE-SEM) images of the blank cotton fiber matrix (Example 15), Examples 1, 9, 14, and Example 1, showing the moisture wetting / spreading.

[0047] Figure 4 XPS depth profile curves (S-element gradient distribution) for Examples 1, 10, and 3. Detailed Implementation

[0048] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0049] In the description of this invention, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the stated features. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.

[0050] In the description of this invention, the term "for example" is used to mean "used as an example, illustration, or description." Any embodiment described as "for example" in this invention is not necessarily to be construed as being more preferred or advantageous than other embodiments. The following description is provided to enable any person skilled in the art to make and use the invention. Details are set forth in the following description for purposes of explanation. It should be understood that those skilled in the art will recognize that the invention can be made without using these specific details. In other instances, well-known structures and processes will not be described in detail to avoid obscuring the description of the invention with unnecessary detail. Therefore, the invention is not intended to be limited to the embodiments shown, but is consistent with the broadest scope of the principles and features disclosed herein.

[0051] Unless otherwise specified, the experimental methods used in the specific implementation methods are all conventional methods, and the materials and reagents used are all commercially available unless otherwise specified.

[0052] In this invention, unless otherwise specified, "%" represents a percentage by mass; the raw materials and reagents used are all commercially available products.

[0053] Some of the raw materials used in this invention are as follows: I. Cotton Fiber Matrix The cotton fiber matrix A used in this invention is combed cotton fiber with a cellulose mass fraction of 90.8%, a crystallinity of 55.8% for cellulose I crystal structure, an average fiber length of 29.6 mm, and an average linear density of 1.56 dtex.

[0054] The cotton fiber matrix B used in this invention is combed long-staple cotton fiber with a cellulose mass fraction of 97.6%, a crystallinity of 74.3% for the cellulose I crystal structure, an average fiber length of 32.4 mm, and an average linear density of 1.39 dtex.

[0055] The cotton fiber matrix C used in this invention is combed cotton fiber with a cellulose mass fraction of 97.2%, a cellulose I crystal structure crystallinity of 76.8%, an average fiber length of 30.5 mm, and an average linear density of 1.48 dtex.

[0056] II. Compounds with multiboron structures The multi-boron compound A used in this invention is 1,4-phenylenediboric acid with a molecular weight of 165.75 g / mol and a boric acid group content of 12.07 mmol / g.

[0057] The multi-boron compound B used in this invention is 1,3-phenyldiboronic acid with a molecular weight of 165.75 g / mol and a boric acid group content of 12.07 mmol / g.

[0058] The boric acid compound C used in the comparative example of this invention is phenylboronic acid with a molecular weight of 121.93 g / mol and a boric acid group content of 8.20 mmol / g.

[0059] III. First hydrophilic olefin unsaturated monomers The first hydrophilic olefinic unsaturated monomer A used in this invention is 2-hydroxyethyl acrylate (HEA) with a molecular weight of 116.12 g / mol.

[0060] The first hydrophilic olefinic unsaturated monomer B used in this invention is N-hydroxymethylacrylamide with a molecular weight of 101.10 g / mol.

[0061] The first olefinic unsaturated monomer C used in this invention is methyl methacrylate (MMA) with a molecular weight of 100.12 g / mol.

[0062] IV. Second hydrophilic olefin unsaturated monomers The second hydrophilic olefinic unsaturated monomer A used in this invention is 2-acrylamide-2-methylpropanesulfonic acid (AMPS), with a molecular weight of 207.25 g / mol.

[0063] The second hydrophilic olefinic unsaturated monomer B used in this invention is 2-methyl methacrylate sulfonyl ester with a molecular weight of 194.21 g / mol.

[0064] The second olefinic unsaturated monomer C used in this invention is ethyl acrylate (EA) with a molecular weight of 100.12 g / mol.

[0065] V. Free Radical Initiation System The free radical initiator used in this invention is ammonium persulfate.

[0066] The free radical promoter used in this invention is tetramethylethylenediamine.

[0067] VI. Silane precursors and microphase separation inducers The silane precursor used in this invention is tetraethyl orthosilicate (TEOS), with a relative density of 0.933 g / cm³. 3 .

[0068] The microphase separation inducer used in this invention is polyethylene glycol (PEG), with an average molecular weight of 6120, a hydroxyl value of 18.3 mgKOH / g, and a moisture content of 0.12 wt%.

[0069] The microphase separation inducer used in the comparative example of this invention is polyethylene glycol (PEG), with an average molecular weight of 400, a hydroxyl value of 280 mg KOH / g, and a moisture content of 0.15 wt%.

[0070] Example 1: A modified cotton fiber and its preparation method 1. Experimental materials and proportions Cotton fiber matrix: Cotton fiber matrix A (combed cotton fiber, cellulose mass fraction 90.8%, crystallinity 55.8%), 100g (equivalent to approximately 0.560mol of cellulose AGU and approximately 1.680mol of total hydroxyl groups).

[0071] Polyboron-structured compound: Polyboron-structured compound A (1,4-phenylenediboric acid), 0.414 g (approximately 2.50 mmol).

[0072] First hydrophilic monomer: First hydrophilic olefinic unsaturated monomer A (2-hydroxyethyl acrylate, HEA), 1.474 g (12.69 mmol).

[0073] Second hydrophilic monomer: Second hydrophilic olefinic unsaturated monomer A (2-acrylamide-2-methylpropanesulfonic acid, AMPS), 0.526 g (2.54 mmol). (The molar ratio of nonionic to ionic units is 1:0.2).

[0074] Initiation system: ammonium persulfate 0.040g, tetramethylethylenediamine 0.020g.

[0075] Surface microstructure system: 0.80 g tetraethyl orthosilicate (TEOS), 0.15 g polyethylene glycol (PEG, average molecular weight 6120), and 200 mL of dehydrated ethanol / water mixed solvent (volume ratio 4:1).

[0076] 2. Preparation steps and process structure detection (S1–S4) S1. Crosslinking treatment and internal network detection: 100g of pretreated clean cotton fiber matrix A was impregnated in a mixed solution of N,N-dimethylformamide (DMF) / water (liquid ratio 1:15) containing 0.414g of polyboron compound A (1,4-phenylenediboric acid). The solution was ultrasonically impregnated at 50℃ for 30min to allow the polyboron compound to penetrate the amorphous region within the cotton fiber. The temperature was then raised to 90℃ and maintained for 2h to allow the 1,4-phenylenediboric acid to undergo a condensation dehydration reaction with the ortho-hydroxyl groups at the C2 and C3 positions of cellulose, forming a five-membered cyclic borate ester crosslinked structure. After the reaction, the fiber was washed with water and dried.

[0077] Process structure inspection (after S1 is completed): The content of borate ester crosslinked structure in the dried S1 sample was tested to be 0.051 mmol / g; the content was determined by FTIR (1340 cm⁻¹). -1The BO absorbance and 11B solid-state NMR spectroscopy confirmed that boron atoms combined with hydroxyl groups at the C2 and C3 positions to form five-membered cyclic boron ester bonds; combined with ICP-OES elemental analysis to determine the mass fraction of boron, it was calculated that the proportion of cellulose hydroxyl groups involved in cross-linking accounted for 5.12% of the total hydroxyl groups.

[0078] S2, Gradient Grafting and Polymer Layer Detection: An aqueous solution (total mass 2000 g, initial monomer concentration approximately 0.1 wt%) containing 1.474 g HEA, 0.526 g AMPS, and an initiation system (ammonium persulfate / tetramethylethylenediamine) was prepared. S1-treated cotton fibers were immersed in this grafting reaction solution and pre-wetted at 35°C for 20 min to allow the monomer molecules and initiator to fully diffuse and penetrate into the amorphous region within the cotton fibers. Subsequently, the surface of the cotton fibers was rapidly rinsed with a small amount of pre-cooled deionized water under low pressure for 10 s, and an equal volume of deionized water was added to dilute the outer phase of the reaction solution, ensuring that the monomer concentration on the outermost surface of the cotton fibers was significantly lower than that inside. Then, nitrogen was introduced to remove oxygen, and the temperature was raised to 50°C to initiate the graft polymerization reaction for 45 min. After the reaction, unreacted monomers and self-polymers were removed by rinsing.

[0079] Process structure inspection (after S2 is completed): The hydrophilic copolymer grafting amount was calculated to be 2.01 wt% by weighing; the molar ratio of nonionic unit (HEA) to ionic unit (AMPS) was 1:0.20 by XPS combined with argon ion sputtering layer analysis; the grafting density decreased from the inside to the outside along the radial direction of the cotton fiber, and the ratio of the maximum grafting density to the minimum grafting density was 1.51.

[0080] S3, In-situ silane construction: Modified cotton fibers treated with S2 were immersed in a dehydrated ethanol / water mixture containing 0.80 g tetraethyl orthosilicate (TEOS) and 0.15 g polyethylene glycol (PEG, Mw=6120). A trace amount of dilute ammonia was added to adjust the pH to 8.5, and the mixture was stirred and allowed to stand at 25°C for 3 hours. Under the phase separation induced by PEG, the silane precursor underwent selective phase separation hydrolysis and condensation reactions on the surface of the hydrophilic copolymer graft layer, generating silicon-containing nanostructures with specific morphologies.

[0081] S4. Controlled shrinkage and final product morphology / performance testing: The cotton fibers treated with S3 are taken out and placed in an environment of 40°C and 70% relative humidity for 2 hours to gently dehydrate, so that the surface gel and grafted polymer chains produce anisotropic physical stress shrinkage. Then, the temperature is raised to 80°C and dried by blowing for 1 hour to complete the structural curing and stabilization. After washing away the residual PEG with water, the fibers are dried to obtain the modified cotton fiber product.

[0082] 3. Final product macroscopic performance test results (after S4 is completed) The final modified cotton fiber product obtained in Example 1 was characterized and its macroscopic physical properties were tested. Surface multi-scale micro / nano morphology (AFM and SEM measurements): The height difference between adjacent peaks and valleys in the micrometer-scale undulation unit is 0.22 μm, and the projected distance between adjacent peaks and valleys along the fiber surface is 0.65 μm; the height difference between adjacent peaks and valleys in the nanometer-scale undulation unit is 25 nm; the ratio of the height difference between micrometer-scale undulations and nanometer-scale undulations is 8.8; the arithmetic mean roughness Ra = 88 nm. The surface area satisfying the above multi-scale height difference characteristics accounts for 18.5% of the total actual measured area.

[0083] Macroscopic textile and moisture-wicking properties: The single fiber breaking strength retention rate was 94.2% (no obvious strength damage after crosslinking). The water contact angle on the fiber surface drops instantly to 0°.

[0084] Example 2: A modified cotton fiber and its preparation method 1. Experimental materials and proportions Cotton fiber matrix: Cotton fiber matrix B (combed long-staple cotton fiber, cellulose mass fraction 97.6%, crystallinity 74.3%), 100g (equivalent to approximately 0.602 mol of cellulose AGU and approximately 1.806 mol of total hydroxyl groups).

[0085] Polyboron-structured compound: Polyboron-structured compound B (1,3-phenyldiboronic acid), 3.336 g (approximately 20.12 mmol).

[0086] First hydrophilic monomer: First hydrophilic olefinic unsaturated monomer B (N-hydroxymethylacrylamide), 6.852 g (67.77 mmol).

[0087] Second hydrophilic monomer: Second hydrophilic olefinic unsaturated monomer B (2-methyl methacrylate sulfonyl ethyl ester), 19.748 g (101.68 mmol). (The molar ratio of nonionic to ionic units is 1:1.5).

[0088] Initiation system: 0.350 g ammonium persulfate, 0.180 g tetramethylethylenediamine.

[0089] Surface microstructure system: 5.20 g tetraethyl orthosilicate (TEOS), 0.85 g polyethylene glycol (PEG, average molecular weight 6120), and 200 mL of dehydrated ethanol / water mixed solvent (volume ratio 4:1).

[0090] 2. Preparation steps and process structure detection (S1–S4) S1. Crosslinking treatment and internal network detection: 100g of pretreated clean cotton fiber matrix B was impregnated in a DMF / water mixture (liquid ratio 1:15) containing 3.336g of a polyboron compound B (1,3-phenylenediboric acid) and ultrasonically impregnated at 40℃ for 25min to allow the polyboron compound to penetrate into the long-staple cotton fiber. The temperature was then raised to 95℃ and maintained for 2.5h to allow the 1,3-phenylenediboric acid to crosslink with the ortho-hydroxyl groups at the C2 and C3 positions of cellulose, forming a five-membered cyclic borate ester bond. After the reaction, the fibers were thoroughly washed with water and dried.

[0091] Process structure inspection (after S1 is completed): The content of borate ester crosslinked structure in the dried S1 sample was determined to be 0.392 mmol / g; the content was analyzed by FTIR (1338 cm⁻¹). -1 The presence of the five-membered ring structure was confirmed by the absorption at a certain point and the 11B solid-state nuclear magnetic resonance spectroscopy. Combined with the boron content measured by ICP-OES, it was calculated that the proportion of cellulose hydroxyl groups involved in cross-linking accounted for 19.64% of the total hydroxyl groups (which meets the limit of 5%-20%).

[0092] S2, Gradient Grafting and Polymer Layer Detection: An aqueous solution containing 6.852 g N-hydroxymethylacrylamide, 19.748 g ethyl sulfonate 2-methacrylate, and an initiator system (total mass 1000 g, initial monomer concentration approximately 2.66 wt%) was prepared. S1-treated cotton fibers were immersed in the grafting reaction solution and pre-wetted at 38°C for 15 min to allow the monomers to penetrate the fibers. The surface was then rinsed with low-pressure deionized water for 5 s to appropriately dilute the external phase. After nitrogen impregnation to remove oxygen, the temperature was raised to 58°C and reacted for 75 min. After the reaction was complete, unreacted substances and self-polymers were removed by washing.

[0093] Process structure inspection (after S2 is completed): The gravimetric method determined the grafting amount of the hydrophilic copolymer to be 14.82 wt%; XPS combined with argon ion sputtering layer analysis showed that the molar ratio of nonionic units to ionic units was 1:1.48; the measurement showed a decreasing gradient from the inside to the outside along the radial direction of the cotton fiber, and the ratio of the maximum grafting density to the minimum grafting density was 2.94.

[0094] S3, In-situ silane construction: S2-treated modified cotton fibers were immersed in a dehydrated ethanol / water mixture containing 5.20 g tetraethyl orthosilicate (TEOS) and 0.85 g polyethylene glycol (PEG, Mw=6120). Dilute ammonia was added to adjust the pH to 9.0, and the reaction was carried out at 30 °C for 4 h. Under the action of the precursor and the microphase separation inducer, silanes underwent phase separation hydrolysis condensation, generating silicon-containing nanostructures on the surface.

[0095] S4. Controlled shrinkage and final product morphology / performance testing: The cotton fibers treated with S3 were taken out and placed in an environment of 45°C and 65% relative humidity for gentle dehydration for 2.5 hours to induce anisotropic shrinkage of the surface layer; then the temperature was raised to 85°C and dried for 1.5 hours. After washing to remove residual PEG, the fibers were dried to obtain the modified cotton fiber product.

[0096] 3. Final product macroscopic performance test results (after S4 is completed) Macroscopic properties and surface morphology of the modified cotton fiber product from Example 2 were tested: Surface multi-scale micro / nano morphology (AFM and SEM measurements): The height difference between adjacent peaks and valleys in the micron-scale undulation unit is 0.94 μm, and the projected distance between adjacent peaks and valleys along the fiber surface is 2.82 μm; the height difference between adjacent peaks and valleys in the nano-scale undulation unit is 188 nm; the ratio of the height difference between micron-scale undulation and nano-scale undulation is 4.89; the arithmetic mean roughness Ra = 485 nm; the surface area that satisfies the above multi-scale height difference characteristics accounts for 68.2% of the total actual measured area.

[0097] Macroscopic textile and moisture-wicking properties: The single-fiber breaking strength retention rate was 91.8%; Dynamic liquid moisture transport (MMT) tests showed that the combined effect of moisture diffusion rate and liquid water penetration on the fiber surface was significantly better than that on raw cotton.

[0098] Example 3: Preparation of modified cotton fibers 1. Differences from Example 1 (Raw Materials and Procedures) Raw material difference: Cotton fiber matrix A (100g) was replaced with cotton fiber matrix C (combed cotton fiber, cellulose mass fraction 97.2%, crystallinity 76.8%), 100g (equivalent to approximately 0.599mol of cellulose AGU and approximately 1.797mol of total hydroxyl groups). The amount of polyboron compound A was slightly adjusted to 0.443g (approximately 2.67mmol) to ensure that the crosslinking index was comparable to that of Example 1.

[0099] Process steps: The specific operating conditions, grafting monomer ratios, and silane surface construction systems for S1–S4 are exactly the same as in Example 1.

[0100] 2. Preparation steps and process structure detection (S1–S4) Process testing after S1 completion: the borate ester crosslinking structure content was 0.038 mmol / g; FTIR and 11B solid-state NMR characterization confirmed the formation of five-membered cyclic borate ester bonds; the proportion of cellulose hydroxyl groups involved in crosslinking accounted for 3.82% of the total hydroxyl groups.

[0101] Process testing after S2 completion: The amount of hydrophilic copolymer grafting was 1.42 wt%; the molar ratio of nonionic unit (HEA) to ionic unit (AMPS) was 1:0.20; and the ratio of maximum radial grafting density to minimum radial grafting density was 3.45.

[0102] 3. Final product macroscopic performance test results (after S4 is completed) Surface multi-scale micro / nano morphology (AFM and SEM measurements): The height difference between adjacent peaks and valleys in the micron-scale undulation unit is 0.18 μm, and the projected distance between adjacent peaks and valleys along the fiber surface is 0.45 μm; the height difference between adjacent peaks and valleys in the nano-scale undulation unit is 18 nm; the arithmetic mean roughness Ra = 72 nm; the area that satisfies the multi-scale height difference characteristics accounts for 11.8% of the total actual measured area.

[0103] Macroscopic textile and moisture-wicking properties: The single fiber breaking strength retention rate is 83.5%; the water contact angle on the fiber surface is 38.5°.

[0104] Example 4: Using monofunctional phenylboronic acid 1. Differences from Example 1 Replace compound A with 0.305 g of phenylboronic acid (boronic acid compound C), and the remaining steps and monomer ratios are the same as in Example 1.

[0105] 2. Process structure inspection (S1–S2) S1 detection: No polymer cross-linking network was detected in the sample, only single-molecule end-group blocking was detected, the content of borate ester cross-linking structure was 0 mmol / g, and the proportion of hydroxyl groups involved in cross-linking was 0%.

[0106] S2 test: grafting amount is 2.02wt%, monomer molar ratio is 1:0.20, and radial gradient ratio is 1.50.

[0107] 3. Final product macroscopic performance test results (after S4 is completed) Surface morphology: Ra=85nm, satisfying the requirement that the characteristic region area accounts for 17.8%.

[0108] Macroscopic properties: Due to the lack of dynamic cross-linking network between molecular chains, the breaking strength of single fibers is severely reduced (strength retention rate is only 81.5%); under repeated bending and humid heat conditions, the fibers have no adaptive stress dissipation ability, and the wrinkle recovery angle is significantly lower than that of Example 1.

[0109] Original Example 5: Using hydrophobic first monomer MMA 1. Differences from Example 1 The first hydrophilic monomer A (HEA) was replaced with 1.271g of hydrophobic monomer MMA (monomer C), and the remaining steps were the same as in Example 1.

[0110] 2. Process structure inspection (S1–S2) S1 detection: cross-linking content 0.051 mmol / g, hydroxyl group involved in cross-linking 5.10%.

[0111] S2 detection: grafting amount is 2.00wt%; molar ratio of MMA to AMPS is 1:0.20; due to the poor affinity of hydrophobic monomer MMA for water, radial diffusion is hindered, and the gradient ratio drops to 1.15.

[0112] 3. Final product macroscopic performance test results (after S4 is completed) Surface morphology: Ra=82nm, which satisfies the characteristic region area ratio of 16.2%.

[0113] Macroscopic properties: Due to the introduction of hydrophobic segments of methyl methacrylate into the grafted layer, the non-ionic hydration channels are lost, the water contact angle increases to 68°, the water diffusion rate decreases significantly, and it is very easy to form localized retained droplets.

[0114] Example 6: Using a hydrophobic second monomer EA 1. Differences from Example 1 The second hydrophilic monomer A (AMPS) was replaced with 0.254g of hydrophobic monomer EA (monomer C), and the remaining steps were the same as in Example 1.

[0115] 2. Process structure inspection (S1–S2) S1 detection: cross-linking content 0.051 mmol / g, with hydroxyl groups participating in cross-linking accounting for 5.08%.

[0116] S2 test: grafting amount was 1.98 wt%; HEA to EA molar ratio was 1:0.20; radial gradient ratio was 1.48.

[0117] 3. Final product macroscopic performance test results (after S4 is completed) Surface morphology: Ra=86nm, satisfying the requirement that the area of ​​the characteristic region accounts for 17.5%.

[0118] Macroscopic performance: Lacking ionic strong hydration groups (such as sulfonic acid groups), it has extremely poor initial capture ability under conditions of trace amounts of sweat and polar liquids, with an initial contact angle of 45° (it takes about 8 seconds to fully wet).

[0119] Example 7: Simultaneous use of dual hydrophobic monomers MMA / EA 1. Differences from Example 1 The first and second hydrophilic monomers were completely replaced with hydrophobic monomers MMA (1.271g) and EA (0.254g), and the remaining steps were the same as in Example 1.

[0120] 2. Process structure inspection (S1–S2) S1 detection: cross-linking content 0.051 mmol / g, with hydroxyl groups participating in cross-linking accounting for 5.11%.

[0121] S2 test: grafting amount was 1.99 wt%; molar ratio of MMA to EA was 1:0.20; radial gradient was extremely insignificant (gradient ratio was only 1.08).

[0122] 3. Final product macroscopic performance test results (after S4 is completed) Surface morphology: Ra=80nm, satisfying the requirement that the area of ​​the characteristic region accounts for 15.1%.

[0123] Macroscopic performance: The grafted layer is completely hydrophobic, with a surface water contact angle of up to 92°, completely losing its moisture absorption and quick-drying function, and hindering the moisture transport of the internal capillaries.

[0124] Example 8: Using the low molecular weight microphase separation inducer PEG-400 1. Differences from Example 1 Replace the microphase separation inducer (PEG, Mw=6120) in step S3 with 0.15g of low molecular weight PEG (Mw=400, hydroxyl value 280mgKOH / g), and the remaining steps are the same as in Example 1.

[0125] 2. Process structure inspection (S1–S2) S1 detection: cross-linking content 0.051 mmol / g, with hydroxyl groups participating in cross-linking accounting for 5.12%.

[0126] S2 test results: grafting amount 2.01wt%, monomer molar ratio 1:0.20, radial gradient ratio 1.51.

[0127] 3. Final product macroscopic performance test results (after S4 is completed) Multi-scale micro-nano morphology of the surface (AFM and SEM tests): Because low molecular weight PEG-400 cannot form thermodynamic phase separation self-assembly with water / ethanol and TEOS condensation polymers, it only forms a flat and smooth silica thin layer on the surface.

[0128] Micrometer-level undulation height difference <0.05μm, nanometer-level undulation height difference <5nm; arithmetic mean roughness Ra=18nm; The area that satisfies the characteristic height difference accounts for only 2.1% (which cannot form an effective multi-scale undulation).

[0129] Macroscopic performance: After water reaches the surface, it cannot quickly form a thin liquid film and spread out. The liquid contact area is small, and the evaporation rate is reduced by more than 45% compared with Example 1.

[0130] Example 9: Cancellation of S1 crosslinking treatment 1. Differences from Example 1 Step S1 is omitted, and the uncrosslinked natural cotton fiber matrix A is directly subjected to gradient grafting in step S2, silane construction in step S3, and controlled shrinkage in step S4.

[0131] 2. Process structure inspection (S1–S2) S1 detection: Untreated, crosslinking content 0 mmol / g.

[0132] S2 test: grafting amount is 2.03wt%, monomer molar ratio is 1:0.20, and radial gradient ratio is 1.50.

[0133] 3. Final product macroscopic performance test results (after S4 is completed) Surface morphology: Ra=86nm, which satisfies the characteristic region area ratio of 18.1%.

[0134] Macroscopic properties: Due to the lack of a borate ester cross-linking network within the fiber, the cotton fiber molecular chains undergo severe and large-scale irreversible slippage during moisture absorption and drying shrinkage. After five washes, the internal capillary channels close and collapse over a large area, and the residual deformation after repeated bending is extremely large, resulting in a complete loss of the fabric's wrinkle resistance.

[0135] Example 10: Cancellation of S2 pre-wetting cleaning 1. Differences from Example 1 The "pre-impregnation + surface rinsing" process in S2 is cancelled. Instead, the fibers are directly immersed in the grafting solution and heated to react, forming a uniform grafted layer. The remaining steps are the same as in Example 1.

[0136] 2. Process structure inspection (S1–S2) S1 detection: cross-linking content 0.051 mmol / g, with hydroxyl groups participating in cross-linking accounting for 5.12%.

[0137] S2 testing: the grafting amount was controlled at 2.02 wt%, and the monomer molar ratio was 1:0.20; the layer analysis showed that the grafting density was uniformly distributed radially, and the ratio of the maximum to the minimum grafting density was only 1.04 (no gradient was formed).

[0138] 3. Final product macroscopic performance test results (after S4 is completed) Surface morphology: Ra=85nm, satisfying the requirement that the characteristic region area accounts for 17.9%.

[0139] Macroscopic performance: After moisture enters the fiber, there is a lack of wettability gradient driving force with "high inside and low outside". Moisture transfer is characterized by disordered diffusion to the surroundings and remaining inside. It cannot form a continuous moisture-conducting process of "absorption-directional migration-surface spreading", and the quick-drying time is extended by nearly 100%.

[0140] Example 11: Using only a single-step nonionic monomer HEA 1. Differences from Example 1 In step S2, the second hydrophilic monomer AMPS is not added; only the first hydrophilic monomer HEA (2.00 g) is added, and the total grafting amount is controlled to be consistent with that in Example 1. The remaining steps are the same as in Example 1.

[0141] 2. Process structure inspection (S1–S2) S1 detection: cross-linking content 0.051 mmol / g, with hydroxyl groups participating in cross-linking accounting for 5.12%.

[0142] S2 detection: grafting amount is 2.01wt%; monomer molar ratio is 1:0 (lacking ionic units); radial gradient ratio is 1.50.

[0143] 3. Final product macroscopic performance test results (after S4 is completed) Surface morphology: Ra=87nm, which satisfies the characteristic region area ratio of 18.3%.

[0144] Macroscopic performance: Lacking the hydration effect of ionic groups (sulfonic acid groups), it is significantly insufficient in capturing and rapidly wetting high-salt sweat, resulting in a slow initial wetting rate.

[0145] Example 12: Using only single-step ionic monomers AMPS 1. Differences from Example 1 In step S2, the first hydrophilic monomer HEA is not added; only the second hydrophilic monomer AMPS (2.00 g) is added, and the total grafting amount is controlled to be consistent with that in Example 1. The remaining steps are the same as in Example 1.

[0146] 2. Process structure inspection (S1–S2) S1 detection: cross-linking content 0.051 mmol / g, with hydroxyl groups participating in cross-linking accounting for 5.12%.

[0147] S2 detection: grafting amount is 1.99wt%; monomer molar ratio is 0:1 (lacking nonionic units); radial gradient ratio is 1.49.

[0148] 3. Final product macroscopic performance test results (after S4 is completed) Surface morphology: Ra=86nm, satisfying the requirement of a characteristic region area ratio of 18.0%.

[0149] Macroscopic performance: Lacking nonionic hydrogen bond hydration channels, water molecules are tightly bound locally by strong ionic groups, resulting in a sharp increase in the resistance to the migration of internal water to the outer surface, a long retention time, and an inability to dry quickly.

[0150] Example 13: Eliminating the S3 silane construction step 1. Differences from Example 1 The S3 silane in-situ construction step was omitted. After S1 crosslinking and S2 gradient grafting, S4 drying was carried out directly.

[0151] 2. Process structure inspection (S1–S2) S1 detection: cross-linking content 0.051 mmol / g, with hydroxyl groups participating in cross-linking accounting for 5.12%.

[0152] S2 test results: grafting amount 2.01wt%, monomer molar ratio 1:0.20, radial gradient ratio 1.51.

[0153] 3. Final product macroscopic performance test results (after S4 is completed) Multi-scale micro-nano morphology of the surface (AFM and SEM tests): The surface only has the original weak grooves of natural cotton fibers.

[0154] The height difference of the micron-level undulations is <0.08μm, with no nano-level undulations; Ra=32nm; the area ratio that satisfies the characteristic height difference is 0%.

[0155] Macroscopic properties: After moisture reaches the surface, it cannot spread quickly to form a thin film, the liquid-gas contact area is small, and the evaporation rate is slow.

[0156] Example 14: Eliminating the S4 staged dehydration and drying 1. Differences from Example 1 In step S4, the phased shrinkage process of "gentle dehydration at 40℃ and 70%RH for 2 hours" is cancelled, and it is replaced by direct drying and curing in a 105℃ oven in one go.

[0157] 2. Process structure inspection (S1–S2) S1 detection: cross-linking content 0.051 mmol / g, with hydroxyl groups participating in cross-linking accounting for 5.12%.

[0158] S2 test results: grafting amount 2.01wt%, monomer molar ratio 1:0.20, radial gradient ratio 1.51.

[0159] 3. Final product macroscopic performance test results (after S4 is completed) Multi-scale micro-nano morphology of the surface (AFM and SEM tests): Due to the rapid boiling and evaporation of water, the silica gel on the surface collapsed and shattered directly without slow-release anisotropic shrinkage, and failed to form micro / nano synergistic undulations.

[0160] The height difference of the micron-level undulations is 0.12 μm, while the nano-level undulations exhibit disordered aggregated particles; Ra = 58 nm; the area that satisfies the multi-scale height difference characteristics accounts for only 4.2%.

[0161] Macroscopic properties: The surface has a rough structure and extremely poor washability. After one wash, a large number of disordered nanoparticles on the surface fall off, and the evaporation rate drops rapidly.

[0162] Example 15: Blank natural cotton fiber matrix 1. Differences from Example 1 Blank natural cotton fiber matrix A without any chemical modification or surface treatment is used.

[0163] 2. Process structure inspection (S1–S2) S1 detection: Crosslinking content was 0 mmol / g.

[0164] S2 test: Grafting amount is 0wt%.

[0165] 3. Final product macroscopic performance test results Surface multi-scale micro-nano morphology: It only has the natural ridge-like micro-grooves of natural cotton fibers, Ra=35nm, without multi-scale composite undulations.

[0166] Macroscopic performance: The single fiber breaking strength retention rate was set to 100%. The wrinkle recovery angle is poor, resulting in a large number of residual wrinkles after washing; After absorbing water, the moisture was severely retained in the amorphous area inside the fiber, and the drying time was 2.8 times that of Example 1.

[0167] The 3D topographic maps and cross-sectional profile curves of Examples 1, 9, and 10 are as follows: Figure 1 As shown.

[0168] The FTIR infrared spectra of Examples 1, 2 and blank cotton fiber matrices after S1, S2 and S3 are as follows: Figure 2 As shown.

[0169] Five high-resolution scanning electron microscope (FE-SEM) images of blank cotton fiber matrix (Example 15), Examples 1, 9, 14, and Example 1, showing moisture wetting / spreading, are shown below. Figure 3 As shown.

[0170] XPS depth profile curves (S-element gradient distribution) for Examples 1, 10, and 3 are as follows: Figure 4 As shown.

[0171] Test Example 1 The cotton fibers from Examples 1-15 were woven into fabrics using the same process (plain weave, warp and weft density 133×72 threads / 10cm, fabric weight 120g / m2) for testing.

[0172] Test methods 1. Dynamic transport properties of liquid water (MMT method) Method: According to GB / T 21655.2-2019, the fabric was placed between the upper and lower electrodes of a liquid water dynamic transfer tester, and 0.2 mL of test solution was injected into the upper surface. The dynamic diffusion process of liquid water on the wetted surface (inner skin-contact layer) and the transfer surface (outer layer) of the fabric was measured, and the unidirectional transfer index (OMC, %) was calculated.

[0173] 2. Moisture evaporation rate and drying time Method: According to GB / T 21655.1-2023, 0.2 mL of distilled water was dropped onto the center of the suspended fabric, and the sample mass change curve over time was recorded. The amount of water evaporated per unit time (evaporation rate, g / h) and the time required for the water droplet to dry completely (drying time, min) were calculated.

[0174] 3. Fabric Wrinkle Recovery Angle (WRA) Method: According to GB / T 3819-1997 (rapid elasticity method), the fabric was cut into 15mm×40mm samples, with 5 samples taken in each of the warp and weft directions. After holding under 10N pressure for 5 minutes, the pressure was released, and the recovery angle was measured by standing for 5 minutes on an angle measuring instrument. The result was the sum of the warp and weft recovery angles (WRA, warp + weft, °). The test included both dry and wet conditions (after immersion in water).

[0175] 4. Fabric breaking strength and tearing strength Methods: The breaking strength was calculated according to GB / T 3923.1-2013 (strip method, tensile speed 100 mm / min), and the warp breaking strength retention rate (%) relative to the unmodified original fabric was calculated; the tearing strength was calculated according to GB / T 3917.2-2009 (trousers test method), and the average warp tearing strength (N) was recorded.

[0176] 5. Washing durability (retested after 50 washes) Method: Following GB / T 8629-2017 (4N standard washing procedure, using standard detergent), the fabric was washed continuously for 50 cycles and then laid flat to dry. The MMT one-way transfer index (OMC) was then re-measured. 50 ) and wet wrinkle recovery angle (WRA) 50 ), calculate the performance degradation rate (expressed as OMC degradation rate: ΔOMC=[(OMC0-OMC 50 ) / OMC0]×100%.

[0177] The results are shown in Tables 1, 2, and 3.

[0178] Table 1 ; Table 2 ; Table 3 ; Note: In Table 1, a negative MMT One-Way Transfer Index (OMC) indicates that moisture is trapped in the reverse direction or cannot migrate unidirectionally from the inner layer to the outer layer; the lower the OMC decay rate, the better the wash resistance.

[0179] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.

Claims

1. A modified cotton fiber, characterized in that, The invention includes a cotton fiber matrix, wherein a borate ester crosslinking structure is formed inside the cotton fiber matrix, a hydrophilic copolymer is grafted onto the surface and near-surface layer of the cotton fiber matrix, and a micro-nano rough structure is formed on the outer surface of the cotton fiber. The borate ester crosslinking structure is formed by a polyboron structure compound having at least two boric acid groups that can form borate ester bonds with the cellulose hydroxyl groups, and the content of the borate ester crosslinking structure is 0.05-0.40 mmol / g; The hydrophilic copolymer is formed by copolymerizing a first hydrophilic olefinic unsaturated monomer and a second hydrophilic olefinic unsaturated monomer. The first hydrophilic olefinic unsaturated monomer and the second hydrophilic olefinic unsaturated monomer respectively form a nonionic hydrophilic structural unit and an ionic hydrophilic structural unit. The nonionic hydrophilic structural unit and the ionic hydrophilic structural unit are distributed along the molecular chain of the hydrophilic copolymer and together constitute a hydrophilic graft structure. The grafting amount of the hydrophilic copolymer is 2wt%-15wt%; the hydrophilic copolymer forms a decreasing grafting density gradient from the inside to the outside along the radial direction of the cotton fiber, and the ratio of the maximum grafting density to the minimum grafting density of the hydrophilic copolymer in the radial direction of the cotton fiber is 1.5-3.

0. The outer surface of the cotton fiber has a multi-scale surface undulation structure. The height difference between adjacent peaks and valleys of the micron-scale undulation units of the multi-scale surface undulation structure is 0.2-1.0 μm, and the projection distance between adjacent peaks and valleys along the surface of the cotton fiber is 0.5-3.0 μm. The surface of the micron-scale undulation units further has nano-scale undulations, and the height difference between adjacent peaks and valleys of the nano-scale undulations is 20-200 nm. The arithmetic mean roughness Ra of the outer surface of the cotton fiber is 80-500 nm. In the outer surface of the cotton fiber, the surface region that satisfies the height difference characteristics at the micron and / or nanoscale accounts for 15%-70% of the total area of ​​the outer surface of the cotton fiber.

2. The modified cotton fiber according to claim 1, characterized in that, The cotton fiber matrix is ​​natural cotton fiber, the cellulose mass fraction in the cotton fiber matrix is ​​90%-98%, and the cotton fiber matrix has a cellulose I crystal structure with a crystallinity of 55%-75%.

3. The modified cotton fiber according to claim 1, characterized in that, In the borate ester crosslinked structure, boron atoms react with the ortho-hydroxyl groups at the C2 and C3 positions of cellulose to form a five-membered cyclic borate ester bond.

4. The modified cotton fiber according to claim 3, characterized in that, In the cotton fiber matrix, the cellulose hydroxyl groups that participate in the formation of the borate ester crosslinking structure account for 5-20% of the total cellulose hydroxyl groups.

5. The modified cotton fiber according to claim 1, characterized in that, In the hydrophilic copolymer, the molar ratio of nonionic hydrophilic structural units derived from the first hydrophilic olefin unsaturated monomer to ionic hydrophilic structural units derived from the second hydrophilic olefin unsaturated monomer is 1:0.2-1:1.

5.

6. The modified cotton fiber according to claim 5, characterized in that, The weight-average molecular weight of the hydrophilic copolymer is 5000-50000; the first hydrophilic olefin unsaturated monomer is an olefin unsaturated monomer with a nonionic hydrophilic structure, and the second hydrophilic olefin unsaturated monomer is an olefin unsaturated monomer with an ionic hydrophilic structure.

7. The modified cotton fiber according to claim 1, characterized in that, The ratio of the height difference between adjacent peaks and valleys of the micrometer-scale undulation unit to the height difference between adjacent peaks and valleys of the nanometer-scale undulation is 5-50; in the actual measurement area on the outer surface of the cotton fiber, the area with the micrometer-scale undulation and / or nanometer-scale undulation accounts for 15-70% of the total area of ​​the actual measurement area.

8. The modified cotton fiber according to claim 1, characterized in that, The micro-nano rough structure is formed by introducing a hydrolyzable silane precursor and a pore-inducing agent onto the surface of the hydrophilic copolymer graft layer, followed by phase separation, hydrolysis, and condensation to form a silicon-containing nanostructure, and then undergoing controlled shrinkage treatment.

9. A method for preparing modified cotton fiber according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Crosslinking treatment: The cotton fiber is impregnated in a crosslinking solution containing the multiboron structure compound, so that the multiboron structure compound penetrates into the cotton fiber and undergoes a borate esterification reaction with the cellulose hydroxyl groups to form a borate ester crosslinking structure. The content of the borate ester crosslinking structure is controlled to be 0.05-0.40 mmol / g. S2, Gradient Grafting: The cotton fibers treated in S1 are immersed in a grafting reaction solution containing the first hydrophilic olefinic unsaturated monomer, the second hydrophilic olefinic unsaturated monomer, and a free radical initiator. Pre-wetting is first performed at 30-40℃ for 10-30 min to allow the monomers to fully penetrate the cotton fibers. Then, the monomer concentration on the outermost surface of the cotton fibers is reduced by surface cleaning or dilution. Grafting polymerization is then carried out at 45-60℃ for 20-90 min, resulting in a decreasing grafting density gradient of the hydrophilic copolymer along the radial direction of the cotton fibers from the inside out. The grafting amount of the hydrophilic copolymer is controlled at 2-15 wt%, and the ratio of the maximum grafting density to the minimum grafting density is controlled at 1.5-3.

0. S3, In-situ construction of silane: Cotton fibers treated with S2 are contacted with a silane precursor containing hydrolyzable alkoxy groups and a pore-inducing agent, so that the silane precursor undergoes phase separation hydrolysis and condensation on the surface of the hydrophilic copolymer graft layer to form a silicon-containing nanostructure. S4. Controlled shrinkage: The cotton fibers treated in S3 are dehydrated and dried in stages to cause controlled shrinkage of the hydrophilic copolymer graft layer and its surface silicon-containing nanostructures, forming a multi-scale surface undulation structure on the outer surface of the cotton fibers, thus obtaining the modified cotton fibers.

10. A cotton fabric that is easy to care for, wrinkle-resistant, moisture-wicking, and quick-drying, characterized in that... The cotton fabric is formed by spinning and weaving the modified cotton fibers as described in any one of claims 1-8.